Movement and distribution of coconut scale insect, Aspidiotus rigidus Reyne (Hemiptera Diaspididae) relative to climatic changes - Cugal, Lisa Mae T. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The Philippines is an agricultural country recognized as the second largest top coconut producer worldwide. It has suffered devastating coconut scale insect (CSI) outbreaks caused by an invasive insect, Aspidiotus rigidus, which has inflicted substantial ecological and economic losses. Despite the threats this invasive insect poses, knowledge of its biology and distribution is still limited. In this study, an ecological niche model (ENM) was developed using Maximum Entropy (MaxEnt) algorithm to predict the current and future habitat suitability of A. rigidus in the Philippines. In this study, ENMs for its plant hosts, Cocos nucifera (coconut) and Musa sp. (banana), were developed to assess potential restrictions imposed by host availability on A. rigidus distribution. Performance of the models based on climate-only variables and on climate and biotic interactions were evaluated. Future projections were made for years 2050 and 2070 using General Circulation Model (GCM) for three Representative Concentration Pathways (RCP 2.6, RCP 4.5, and RCP 8.5). Results for the hosts ? but not for the parasite ? reject the Eltonian Noise Hypothesis (ENH), suggesting that biotic interactions can affect species geographic distribution. This study supported the notion that biotic interactions can improve ecological niche models. Furthermore, CSI was predicted to be suitable in areas that are unsuitable or poorly suitable for coconuts. Therefore, host plant availability does not restrict the distribution of the CSI. For years 2050 and 2070, highly suitable areas for A. rigidus and C. nucifera were predicted to increase or expand but change in the suitability levels of A. rigidus was more pronounced than in C. nucifera. This suggests faster spread of the parasite as more areas become more suitable for habitation, implying a higher risk of another coconut scale insect attack. These findings will be useful in implementing management strategies to prevent future outbreaks, control spread, and identify opportunities for eradication